English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2x^2 - 9y^2 = 17
2(3y + 4)^2 - 9y^2 = 17
9y^2 + 48y + 15 = 0
3y^2 + 16y + 5 = 0
3y^2 + 15y + y + 5 = 0
3y(y +5) + 1(y + 5) = 0
(y + 5)(3y + 1) = 0
y = -5 and y = -1/3

x = 3y + 4
y = -5, x = - 11
y = -1/3, x = 3
The answer is correct, i just have to figure out the workings

2007-01-07 03:11:32 · 2 answers · asked by Lorraine T 1 in Science & Mathematics Mathematics

2 answers

From your second line:

When you expand (3y +4)^2 = 9y^2 + 24y + 16...then you must mulitply by the 2 out front...

18y^2 + 48y + 32 - 9y^2 = 17
9y^2 + 48y + 32 - 17 = 0
9y^2 + 48y + 15 = 0

2007-01-07 03:14:36 · answer #1 · answered by keely_66 3 · 0 0

its not too difficult :i think u should take some good classes about simplification

actually u missed the step which is after urs 2nd step

which is
2(9y^2+24y+16)-9y^2-17=0

then just multiply this 2 to the term in bracket
18y^2-48y+32-9y^2-17=0

9y^2+48y+15=0

3y^2+16y+15=0

u can proceed after that

2007-01-07 11:33:43 · answer #2 · answered by HAIDER I 1 · 0 0

fedest.com, questions and answers